Implementasi Teori Konstruktivisme dalam Pembelajaran Matematika di Rumah untuk Anak Usia Dini Pasca Pandemi Covid-19 - Jahring Jahring; Marniati Marniati; Nasruddin Nasruddin; Armin Armin; Lukman Lukman; Andra Aprisal; I KD Indra Purnomo; Ridhonul Rahman; Pingky Hastuti; Indrawaty Indrawaty; Siska Arhita; Firawati Firawati; Firda Firda (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
Restrictions on learning activities during the COVID-19 pandemic have forced students to study from home. However, it does not mean that the quality of student learning outcomes will decrease. To maintain and even improve students' mathematical abilities and understanding post COVID-19 pandemic, constructivism learning was applied to mathematics learning at home in Puundoho village, North Pakue District, North Kolaka Regency, Southeast Sulawesi. Constructivism learning helps students in building mathematical concepts using their own abilities through an internalization process using prior knowledge. Activities are carried out in three stages, namely planning, implementation and reporting of activities. The form of activity is the application of constructivism learning in mathematics learning at home which aims to maintain the quality of student learning outcomes, as well as improve students' abilities and understanding after the COVID-19 pandemic. The results obtained are the level of students' ability and understanding of mathematics which is indicated by the ease with which they can answer correctly each given question.